(untitled) (Research, Society and Development, 2022)
Objective: to map inspection instruments for children and hebiatric care services. Method: This research protocol is based on the manual found in Joanna Briggs Institute, following the checklist of the Preferred Reporting Items for Systematic Review and Meta-Analyses - The extension for Scoping Reviews Search and data collection will be carried out in October 2022 with the descriptors Health Science and Medical Subject Headings. The selection of studies will be made independently by two researchers. The result will be presented in tables and figures and weighted using thematic analysis.